The Impact of the Treaty of Hudaybiyyah on the Spread of Islam in the Arabian Peninsula - HAMIDI, Hilmi Fauzan (PT. Keberlanjutan Strategis Indonesia, 2024)
Purpose:This research aims to analyze Muslims' main goals in the Treaty of Hudaibiyah and its impact on the relationship between Muslims and the Quraysh. The study focuses on the establishment of four points of the agreement, including a ceasefire, freedom of affiliation, rules for the return of individuals, and permission for pilgrimage the following year. The results of these negotiations caused Muslims to be disappointed.Methodology:This research uses a historical research method that consists of four stages: heuristics (gathering sources), criticism (selecting data), interpretation (interpreting data), and historiography (writing history).Findings:The research findings concluded that the Treaty of Hudaibiyah significantly impacted the spread of Islamic teachings in the Arabian Peninsula. With the agreement on a ceasefire, Muslims were able to spread the teachings of Islam freely. The Prophet Muhammad (peace be upon him) responded to the agreement by sending letters to the kings in Arabia and surrounding areas.Implication:The Treaty of Hudaybiyyah was a major factor in the liberation of the city of Mecca. It happened when the Banu Bakr, who was part of the treaty with the Quraysh, attacked Khuza’ah, who was part of the Islamic group. With the treaty broken and invalidated, the Prophet Muhammad (peace be upon him) then ordered 10,000 Muslim troops to head to Mecca with the aim of freeing Mecca from the shackles of disbelief and the ignorant behavior of the Quraysh people.